1999
DOI: 10.1029/98je02554
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Mars Pathfinder Mission: Launch through landing, surface operations, data sets, and science results

Abstract: Abstract. Mars Pathfinder successfully landed at Ares Vailis on July 4, 1997, deployed and navigated a small rover about 100 m clockwise around the lander, and collected data from three science instruments and ten technology experiments. The mission operated for three months and returned 2.3 Gbits of data, including over 16,500 lander and 550 rover images, 16 chemical analyses of rocks and soil, and 8.5 million individual temperature, pressure and wind measurements. Pathfinder is the best known location on Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 45 publications
7
103
0
Order By: Relevance
“…Details regarding observational planning and instrument sequencing can be found in the mission overview description by Golombek et al [1999]. Here, we briefly touch upon the most salient observational details relevant to the study of soils and dust at the landing site.…”
Section: Mars Pathfinder Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details regarding observational planning and instrument sequencing can be found in the mission overview description by Golombek et al [1999]. Here, we briefly touch upon the most salient observational details relevant to the study of soils and dust at the landing site.…”
Section: Mars Pathfinder Observationsmentioning
confidence: 99%
“…On Earth, numerous studies have demonstrated the link between soil physical and chemical properties and environmental conditions (e.g., reviews in the work by Schwertmann and Taylor [1989]; Cornell and Schwertmann [1996]); the working assumption is that similar inferences about environmental conditions on Mars. past and present, can be gleaned 1721 from measurements of the properties of soils found there todayAnalyses of remote sensing data specific to the Mars Pathfinder landing site both prior to and after landing revealed (1) that the site is in a region that is transitional between classical bright (Chryse) and dark (Acidalia) regions [Golombek et a!., 1997a], (2) that the lower albedo and Viking Orbiter red/blue ratio of the region appear to correspond to less bright dust at the Pathfinder site than Viking Lander 1 (VL1) [Golombek et al, 1997b], and (3) that the MPF site also has a greater abundance of dark materials. The dark materials at the MPF site could represent a contribution of "local" material [Larsen et a!., 1999], or could represent a contribution from dark soils not previously sampled by VL1 or VL2, neither of which landed in dark regions or found dark soil deposits at their landing sites.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental requirement of two component physical mixing models to explain chemical variation is that all interelement relationships must correspond to the model [Langmuir et al, 1978]. In terrestrial clastic sediments, where physical mixing unquestionably plays a role, such simple mixing relationships are uncommon and where present are restricted to immobile elements [e.g., McLennan et al, 1993].…”
mentioning
confidence: 99%
“…The Thermal Emission Spectrometer (TES; W29) on MGS has provided compositional constraints for Martian surface materials over areas as small as 3 by 3 km (Christensen et ai, 1998(Christensen et ai, , 2001. TES spectra have revealed two distinct volcanic compositions abundant on the Martian surface: a typical basaltic composition and a slightly more chemically evolved basaltic andésite composition (Bandfield el al., 2000) that is comparable to several rocks at the Mars Pathfinder landing site (Golombek et al, 1999). The TES basalt component has a high concentration in Syrtis Major (Bandfield el al., 2000;Ruff and Christensen, 2002), a classic lowalbedo feature that includes large barchan dunes (Figure 9.8).…”
Section: A Post-mgs Perspective Of Eolian Deposits On Marsmentioning
confidence: 99%